Designing with membranes - Beccarelli, Paolo (Springer International Publishing, 2015)
This contribution offers an introduction to membrane structures and the experimental approach which has characterised this building system since its origins. In particular, the chapter offers an overview of the design approach currently adoptedÂ for tensioned membrane roofs.